Analisis Kadar Air Tanah Dalam Mendukung Pertumbuhan Kelapa Sawit di Kebun PTPN IV Sei Karang - Prananta Tarigan, Yuda; Wiranda Fortunata, Sefri; Latifatusukriah1, Latifatusukriah; Rasyid Nst, Abdullah; Rifky Saputra, Muhammad (JURNAL AGROPLANT, 2025)
This study is based on the importance of understanding soil moisture levels to support oil palm growth, particularly in the PTPN IV Sei Karang plantation in Deli Serdang Regency. Plant growth and environmental balance are greatly influenced by the amount of water in the soil. The objective of this study is to analyse soil moisture content using both direct and indirect measurement methods, and to investigate the relationship between soil moisture content and environmental factors such as rainfall, soil texture, and organic matter content. The study was conducted at two soil depths: 0–20 cm and 20–40 cm. The measurement results showed soil moisture content of 8.69% and 7.52%, respectively. This difference indicates variations in pore size and water-holding capacity across soil layers. Additionally, the findings suggest that soils with fine texture and high organic matter content can retain water more effectively. The research results indicate that the soil conditions at the site support optimal growth for oil palm plants, particularly those with strong and deep roots. This study has significant implications for water management and sustainable agriculture. Information on soil moisture levels can be utilised as a basis for planning irrigation and more efficient and productive land use.